2018
DOI: 10.1002/bem.22127
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic field therapy in the treatment of pain and other symptoms in fibromyalgia: A randomized controlled study

Abstract: Low-energy pulsed electromagnetic field (PEMF) therapy has been suggested as a promising therapy to increase microcirculation, which is of great concern in patients with fibromyalgia. This study evaluated the effectiveness of PEMF therapy on the treatment of fibromyalgia. A group of 108 women with fibromyalgia were allocated to a 12-week treatment period with an active Bio-Electro-Magnetic-Energy-Regulation (BEMER) device and a similar treatment period with an inactive device. Each patient received active and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…PEMF is another non-invasive neuromodulatory technique that uses electromagnetic fields to induce electrical induction to target specific tissues and has been explored as an analgesic technique [33]. Previous studies have found that PEMF enhances tissue recovery and repair via induction of Eddy currents, which may have an effect in gene expression such as the endogenous opioid pathways [54]. Other proposed mechanisms could involve nitric oxide to improve blood flow, calmodulin, or eicosanoid enzymes [55].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 99%
“…PEMF is another non-invasive neuromodulatory technique that uses electromagnetic fields to induce electrical induction to target specific tissues and has been explored as an analgesic technique [33]. Previous studies have found that PEMF enhances tissue recovery and repair via induction of Eddy currents, which may have an effect in gene expression such as the endogenous opioid pathways [54]. Other proposed mechanisms could involve nitric oxide to improve blood flow, calmodulin, or eicosanoid enzymes [55].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 99%
“…Timed Up and Go (TUG) test was used for functional mobility. The TUG uses the time that a person takes to rise from a standard 45 cm chair, walk 3 m, turn around, walk back to the chair, and sit down (13). Two trials performed and the faster of the two is recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Microcirculation is of great concern in patients with FM. Recently low-energy pulsed electromagnetic field therapy was found to increase a promising therapy to increase microcirlulation [ 110 ]; however, neither pain and stiffness were reduced nor functioning was improved by this therapy in women with FM [ 111 ].…”
Section: Therapymentioning
confidence: 99%